Identifying health and wellbeing related information management activities and needs in families with young children - Palmén, Marilla; Korpela, Mikko; Saranto, Kaija (Finnish Journal of eHealth and eWelfare, 2012)
Understanding how families manage health and wellbeing related information in their everyday lives is important in the user-centric design of information and communication technology (ICT) supported services. Using activity theory as a conceptual framework, the aim of this exploratory research was to make visible families’ everyday health and wellbeing information management activities and needs. We applied a qualitative study design using the method of longitudinal virtual focus group discussion with eight households (n=8) over four weeks of time. As a result, we identified nine information management activities and grouped them under three role categories that families with young children play in the Finnish society when seeking health and wellbeing: families as users of health and social services, families in the role of consumers in the market of goods and services, and families in the role of citizens who aspire to a sense of wellbeing in its widest meaning. Furthermore, we identified information management activities with which families felt mostly dissatisfied. The study provides a baseline understanding of everyday information management in families with young children to be applied further in ICT supported family health and wellbeing service development and innovation.